ATTITUDE AND CONDITION OF MODERN FAMILY WITH CHILDFREE BY CHOICE - ชัยวัฒน์ ปภัศร; ธรรมวิชปรีชา พลอยนภัส (Sripatum Review of Humanities and Social Sciences, 2018)
“Childfree by choice” is a popular idea of new modern family, but it causes a continuous low birth rate in the country. This quantitative research analyzes the childfree attitude of couples that had middle to high incomes and lived in the city. The result shows that respondents which have an unsecured work position with high competition, and with high level of anxiety on income tend to want to have a childfree family. Furthermore, the main attitudes of the sample group are the emphasis on free and simple lifestyle, the anxiety over economic impacts resulted from child rearing, and negative influences from the outside society/community that have impacts on raising the family. As for the appropriate policy, the state should provide more financial incentive for child rearing, promote income security especially for self-employed workers, promote working at home, support technology for virtual office, support the simple way of child rearing, reduce competition in learning, and focus on solving social problems in the community. These policies will motivate families in the modern age to want to have children.